The Effectiveness of Career Counseling Model towards the Level of Career Maturity among the Drug Addicts - Amin Al Haadi Shafie; Siti Khadijah Binti Abd Karim; Nurhafizah Binti Mohamad Yasin; Nurul Ashikin Binti Ahmat Miskam; Hishamuddin Abdul Wahab; Mohd Khairul Anuar Rahimi; Nurhafizah Mohd. Sukor; Siti Nubailah Mohd Yusof (Center for Promoting Ideas, USA, 2024)
Indexed by ERA